Prediksi Model 2d Data Magnetotelurik Terbaik Berdasarkan Pendekatan Model Irisan Di Cekungan Tomori dan Sekitarnya - Gusti Muhammad Lucki Junursyah; Dimas Bagus Maulana; Randi Rusdiana (Pusat Survei Geologi, 2019)
2D modeling of magnetotelluric data produce various models that are influenced by noise and differences in coordinate measurement systems with strike directions, so the results are inaccurate. A technique that can be done to identify the accuracy of the data is the rotation analysis based on the overlay model approach. The type of rotation used are strike angle and fix angle. The strike angle rotation is done by maximizing the anti-diagonal impedance value, while the rotation fix angle refers to the isotropic homogeneous earth model by eliminating the static effect on the surface. The overlay model approach is based on the assumption that the distribution of resistivity variations of the rock in the subsurface has same value in various models. 2D modeling used in this analysis consists of three trajectories of correlation results from 30 magnetotelluric measurement points in the Tomori and surrounding areas. The results of the analysis show that the strike angle rotation model is the best model that can be used in the study area with the approach of determination value reaches 0.7735, therefore it can reduce subsurface geological interpretation deviation based on various 2D models.Keywords: Magnetotelluric, impedance rotation, strike angle rotation, fix angle rotation